Digital sociology the reinvention of social research - Marres, Noortje 1975- (Malden, Massachusetts Polity, 2017)
"This provocative new introduction to the field of digital sociology offers a critical overview of interdisciplinary debates about new ways of knowing society that are emerging today at the interface of computing, social research and social life. Digital Sociology introduces key concepts, methods and understandings that currently inform the development of specifically digital forms of social inquiry. Marres assesses the relevance and usefulness of digital methods, data and techniques for the study of sociological phenomena and evaluates the major claim that computation makes possible a new ?science of society?. As Marres argues, the digital does much more than inspire innovation in social research ? it forces us to engage anew with fundamental sociological questions. If digital ways of knowing society are to deliver on their promise, we must learn to appreciate that the digital has the capacity to throw into crisis existing knowledge frameworks and is likely to reconfigure wider relations between sociology, computing, media and their publics. This timely engagement with a key transformation of our times will be indispensable reading for undergraduate and graduate students taking courses in digital sociology, digital media, computing and society"--Provided by publisher.
1. What is digital sociology? 2. What makes digital technologies social? 3. Do we need new methods? 4. Are we researching society or technology? 5. Who are digital sociology's publics? 6. Does digital sociology have problems? References.
Includes bibliographical references and index.
Keywords: Sociology; Social sciences -- Research; Technological innovations -- Social aspects